Arrhythmia analysis in Langendorff perfused hearts significant contribution to model characterisation and validation of arrhythmia definitions - Takács Hedvig; Farkas András (2019)
In this work, we used the isolated, Langendorff perfused heart model for arrhythmia investigations, and the data of the arrhythmia analysis served for clarifying and characterising the physiology of the model and also, to validate arrhythmia definitions. In our first investigation we examined the relationship between ventricular rhythm and coronary flow autoregulation in Langendorff perfused guinea pig hearts. It is a well-known fact, that heart rate affects coronary flow, but the mechanism is complex, especially in experimental settings. We examined whether ventricular irregularity influences coronary flow independently of heart rate. According to our results, during regular rhythm, left ventricular pressure exceeded perfusion pressure and prevented coronary perfusion at peak systole. However, ventricular irregularity significantly increased the number of beats in which left ventricular pressure remained below perfusion pressure, facilitating coronary perfusion. We found that in isolated hearts, cycle length irregularity increases the slope of the positive linear correlation between mean ventricular rate and coronary flow via producing beats in which left ventricular pressure remains below perfusion pressure. This means that changes in rhythm have the capacity to influence coronary flow independently of heart rate in isolated hearts perfused at constant pressure. In our second investigation we examined whether the arrhythmia definitions of Lambeth Conventions I (LC I) and Lambeth Conventions II (LC II) yield the same qualitative results and whether LC II improves inter-observer agreement. Data obtained with arrhythmia definitions of LC I and LC II were compared within and between two independent observers. Applying ventricular fibrillation (VF) definition of LC II significantly increased VF incidence and reduced VF onset time irrespective of treatment by detecting ‘de novo’ VF episodes. Using LC II reduced the number of ventricular tachycardia (VT) episodes and simultaneously increased the number of VF episodes, and thus, LC II masked the significant antifibrillatory effects of flecainide and the high K+ concentration. When VF incidence was tested, a very strong interobserver agreement was found according to LC I, whereas using VF definition of LC II reduced inter-observer agreement. It is concluded that LC II shifts some tachyarrhythmias from VT to VF class. VF definition of LC II may change the conclusion of pharmacological, physiological and pathophysiological arrhythmia investigations and may reduce inter-observer agreement.
Disszertacio
Keywords: klinikai orvostudományok